TRAIL-based therapy in pediatric bone tumors: how to overcome resistance. (February 2015) - Guiho, Romain; Biteau, Kevin; Heymann, Dominique; Redini, Françoise
ABSTRACT : Osteosarcoma and Ewing's sarcoma, the two most frequent malignant primary tumors preferentially arise in children and young adults, and have a poor prognosis. TRAIL represents a promising therapeutic approach for most cancers but in the case of primary bone tumors, osteosarcoma cell lines are highly resistant to this pro-apoptotic cytokine. In addition, another signaling pathway mediating cell proliferation and migration may be even activated in this subset of resistant cells leading to protumoral effect. Therapeutic perspectives are linked to possibility to overcome TRAIL resistance by combining other drugs with TRAIL or death receptors agonistic antibodies. We hypothesized that the bone microenvironment may provide a favorable niche for TRAIL resistance that might be targeted by new resensitizing agents.